Ramos and Teixeira in the 30’s - Sircilli, Fabíola (Paidéia (Ribeirão Preto), 2005)
This article shows the New School movement and authors related to it. We focus on Arthur Ramos, a doctor who worked along with Anísio Teixeira, an eminent activist, when he was the head of the Public Instruction of the Federal District in the 30´s. Ramos, who had strong links with Psychoanalysis, directed the Mental Hygiene Institute that was a department of the municipal administration during Teixeira´s management where a Service of Ortofrenia and Mental Hygiene was implemented. There, Ramos applied Freud, Jung and Adler adjusting their psychological theories to the Brazilian education. Data indicates that the application of psychoanalysis to the education was favored by Teixeira´s Deweyan ideas. This study has its origin in a research based on Ramos books: "Educação e Psicanálise" and "A criança problema".